Improvement of the recipe composition of special-purpose gluten-free chocolate muffins - Shapovalenko, Oleg; Pavliuchenko, Olena; Furmanova, Yuliia; Sharan, Larisa; Kuzmin, Oleg (My University, 2020)
The paper considers how gluten-free flours, in particular, those made from coconuts and brown rice, can be used in the technology of gluten-free chocolate muffins in order to expand the range of special purpose products. Studies by domestic and foreign authors dedicated to using different flour types in today’s gluten-free technologies have been analysed. It has been proved that wheat flour can be fully replaced with gluten-free flour mixtures in the recipe of chocolate muffins. Analysis of the chemical composition of coconut flour has shown its higher fat content, compared with wheat flour, and twice as much protein and dietary fibre (18%). Coconut flour exceeds wheat flour not only in the main macronutrients, but also in the content of the main minerals. Brown rice flour, too, contains more fats and vitamins of the B-group than wheat flour does, and is a source of sodium, magnesium, phosphorus, silicon, and sulphur. It contains up to 80% of starch and, like coconut flour, is gluten-free. Replacing wheat flour in the classical muffin recipe with mixtures of coconut and brown rice flours in the ratios 30:70, 40:60, and 50:50 reduces the moisture content and density of the dough. The moisture content in the finished muffins, too, is lower by 0.7, 1.2, and 1.5% respectively. It has been confirmed that if the gluten-free flour mixture contains over 50% of coconut flour, it reduces the specific volume of resulting muffins and worsens their quality parameters. The Harrington method was used to estimate the comprehensive quality index of the chocolate muffins. This has shown that full substitution of wheat flour for a mixture of glutenfree flours in the ratio 40:60 (coconut flour:brown rice flour) allows achieving the best-balanced sensory characteristics. Gluten-free muffins have a pleasant brown colour of the crust, their crumb is quite soft, homogeneous, and porous, with a balanced taste and an aroma of cocoa combined with light coconut notes.У статті висвітлено питання щодо використання безглютенових видів борошна, а саме кокосового та борошна з коричневого рису, у технології шоколадного кексу «Глютен-фрі» з метою розширення асортименту продуктів спеціального призначення. Проаналізовано наукові праці вітчизняних та закордонних авторів, присвячені використанню різних видів борошна у сучасній технології безглютенової продукції та встановлено можливість повної заміни пшеничного борошна на суміші безглютенового борошна у рецептурному складі шоколадного кексу. Досліджено хімічний склад кокосового і борошна з коричневого рису та з’ясовано, що у порівнянні з пшеничним, кокосове борошно містить значно більше жирів, вдвічі більше білків і клітковини (18%). Поряд з основними макронутрієнтами, кокосове борошно також перевищує пшеничне за вмістом основних мінеральних речовин. Борошно з коричневого рису порівняно з пшеничним борошном також містить більше жирів і характеризується широким спектром вітамінів групи В, є джерелом натрію, магнію, фосфору, кремнію та сірки. Воно містить багато крохмалю (до 80%) і, подібно до кокосового борошна, взагалі не містить глютену. Заміна пшеничного борошна в класичному рецепті шоколадного кексу на суміш кокосового та борошна з коричневого рису у співвідношеннях: 30:70, 40:60 та 50:50 сприяє зменшенню вологості та густини тіста. Зменшується і вміст вологи у готових кексах на 0,7, 1.2 та 1,5% відповідно. Підтверджено, що збільшення у борошняній безглютеновій суміші вмісту кокосового борошна понад 50% сприяє зменшенню питомого об’єму готових виробів та погіршенню їх якісних показників. Визначення комплексного показника якості готових виробів за методом Харрінгтона підтвердили, що запропонована повна заміна пшеничного борошна у рецептурі кексу шоколадного на суміш безглютенового борошна у співвідношенні компонентів: 40:60 (кокосове борошно: борошно з коричневого рису) дозволяє отримати готові кекси з найкращими гармонійними органолептичними якостями. Безглютенові кекси «Глютен-фрі» мають привабливий коричневий колір скоринки, характерну для кексів поверхню, достатньо м'який, однорідний та пористий м’якуш з приємним смаком та ароматом какао, в поєднанні з легкими нотками кокосу.
Keywords: coeliac disease; gluten-free flour; coconut flour; brown rice flour; целіакія; безглютенові вироби; кокосове борошно; борошно з коричневого рису; кафедра технології ресторанної і аюрведичної продукції; кафедра технології зберігання і переробки зерна; кафедра готельно-ресторанної справи